IMPLEMENTATION OF LIFE SKILL EDUCATION IN THE EFFORT TO DEVELOP STUDENTS AT THE INTERNATIONAL STUDENT ISLAMIC BOARDING SCHOOL KH. MAS MANSUR UMS - Risma Silviani Putri; Muthoifin (Profetika: Jurnal Studi Islam, 2023)
Life skills are an important potential in humans that can develop according to individual interests and talents. This research focuses on the implementation of Life Skill Education in the KH International Student Islamic Boarding School. Mas Mansur (PESMA) at the University of Muhammadiyah Surakarta, which aims to empower students with practical skills and self-potential to be ready to face future challenges. PESMA not only teaches religious aspects but also skills that are relevant to the times, combining cognitive, affective, and psychomotor aspects. With a phenomenological approach, this study examines the experiences of students in the Life Skills program which is designed to produce a generation of community leaders. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation. The data sources consist of primary and secondary data, involving the Director, the Nursing Board, PBC and PMC Administrators, as well as students and volunteers. The data was analyzed using the Miles and Huberman method, through the stages of collection, reduction, presentation, and conclusion. The results of the study show that the Life Skills program at PESMA is effective in helping students develop interests and talents, as well as improving their time management, communication, and negotiation skills. Thus, students become individuals who are better prepared to face the world of work after graduation.